Implementasi Kebijakan Layanan Secara Elektronik Pengadaan Kendaraan Dinas Pemerintah Provinsi Jawa Barat - Yusa Djuyandi (Humaniora, 2013)
Electronic Procurement Service (LPSE) is a policy in the procurement of goods and services with internet-based, which facilitates a transparent auction. West Java was chosen as one of the 5 LPSE Center and expected to create transparency and accountability in government management. The purpose of this study is to describe and analyze the LPSE policy implementation, particularly in the procurement of official vehicles in West Java Provincial Government. The research was conducted through observation and interview techniques. Data consisted of primary and secondary data, therefore this research design used qualitative methods. The theory used in this study was the theory of policy implementation. Based on the research, it is known that the policy implementation of LPSE, particularly in the procurement of official vehicles in West Java Provincial Government, is not only able to minimize the corruption potential, but also able to provide a positive impact on the financial condition of local governments. This research conclusion is LPSE policy implementation running well.